PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PT. DENSO INDONESIA - Herningsih, Herningsih (Jurnal Visi Komunikasi, 2020)
The process of achieving organizational goals requires a positive organizational communication climate so that it can connect, regulate and foster the organizational environment regarding the structure and functions of the organization, in a relationship between its members, information processes and organizing processes and organizational culture in order to achieve organizational goals. This research was conducted to determine whether there is an influence of Organizational Communication Climate on the performance of employees of PT. Indonesian Denso. This type of research is quantitative and the nature of the research is causal-comparative analysis. The method used is a survey that has two variables, namely Organizational Communication Climate (x) on Employee Performance (y). The population is employees of PT. Denso Indonesia with probability sampling technique or random sampling. The results of this study using data analysis techniques used in this study are descriptive inferential (probability statistics), and simple linear regression analysis through classical assumption test. Test the hypothesis by using the analysis of the simultaneous influence test (F) to determine the effect of the independent variables together on the dependent variable and the partial test (T) to determine the effect of each independent variable on the dependent variable. This study concludes that trust as an important indicator in the ongoing communication climate makes the company continue to process well, even though each individual still needs an adaptation process in a new company and how to accept and cooperate with new leaders.